2006
DOI: 10.1103/physreve.73.061801
|View full text |Cite
|
Sign up to set email alerts
|

Modified models of polymer phase separation

Abstract: In this paper we discuss continuum models of phase separation in polymer solutions, with emphasis on the thermodynamic foundation of these models. We demand that these models obey a free energy dissipation relation, which in the present context plays the role of the second law of thermodynamics, since the system is isothermal. First, we derive a modified two-fluid model for viscoelastic phase separation from nonequilibrium thermodynamics. Then we study the special case when only diffusion is present, and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 20 publications
3
92
0
Order By: Relevance
“…Tanaka and Araki 19,20 proposed that the quick hydrodynamic reduction of the interfacial area might spontaneously destabilize the phase separated macroscopic domains and induce viscoelastic phase separation. Zhou et al 21 recently reported volume shrinkage, phase inversion, and final complex phase morphologies are caused by diffusional asymmetry of the consistent molecules. It was reported that complex phase separation may take place due to unusual fast growth of domains in the matrix and chemical reaction between the binary mixtures.…”
Section: Introductionmentioning
confidence: 98%
“…Tanaka and Araki 19,20 proposed that the quick hydrodynamic reduction of the interfacial area might spontaneously destabilize the phase separated macroscopic domains and induce viscoelastic phase separation. Zhou et al 21 recently reported volume shrinkage, phase inversion, and final complex phase morphologies are caused by diffusional asymmetry of the consistent molecules. It was reported that complex phase separation may take place due to unusual fast growth of domains in the matrix and chemical reaction between the binary mixtures.…”
Section: Introductionmentioning
confidence: 98%
“…In this regard, Equation 10 can be reduced into a simple mathematical form by setting without affecting the minimization of the free energy. Thus, the interaction parameter also accordingly scales up into the widely reported theoretical range where results in a single well and leads to a double well [23,24,26,32]. As for the dilution parameter , the values can be preliminarily estimated based on the reported swelling ratio values of polymer in PMB.…”
Section: Simulation Environment and Parametersmentioning
confidence: 99%
“…In order to obtain the expression of the free energy, a double-well potential for PMB system can be determined on the basis of the Flory-Huggins free energy of mixing [18][19][20][23][24][25][26]. The Flory-Huggins theory was originally proposed for polymer solutions by taking into account their differences with an ideal solution, i.e.…”
Section: Figure 1 Phase Diagram (A) and Free Energy Curves (B)mentioning
confidence: 99%
“…Phase separation in polymer systems can exhibit a phase inversion. [41][42][43] The phase inversion occurs when the PVME-rich sponge-like structure is broken and the PVME-rich phase changes from being continuous (Fig. 4, layer 4) to being discontinuous (layer 6).…”
Section: Optical Microscopy-morphology Investigationmentioning
confidence: 99%